Pengaturan Pembangkit Listrik Tenaga Uap Batubara Di Indonesia Prespektif Hak Atas Lingkungan Yang Baik Dan Sehat - Theo Alif Wahyu Sabubu (Universitas Islam Indonesia, 2020)
The main problem in this writing is, first, how is the right to a decent and healthy environment in the governance of coal Steam Power Plant (PLTU)?; second, how is the future governance concept? The analysis used is descriptive-qualitative method. There are two approaches to be used in this research, namely the legal approach and the case approach. The results of this study conclude that all the regulations that form the basis of coal PLTU have not provided protection and fulfillment of the right to a decent and healthy environment. The concept of future regulation can be seen from three aspects, namely legal substance, legal culture, and law enforcement. From the aspect of its legal substance, it can be seen that there is no clear and firm regulation regarding coal PLTU, it also requires an instrument on the location and the Clean Air Act. For the legal culture, it is more focused on sustainable and environmentally friendly development. As for the law enforcement, there are still some regulations that are not implemented by the company concerned, for example in coal mining.